FAKTOR-FAKTOR YANG MEMPENGARUHI KELENGKAPAN IMUNISASI DASAR PADA BAYI DI PUSKESMAS BANYUDONO KABUPATEN BOYOLALI - Prasetya Ningrum, Endah; Sulastri, Sulastri (Jurnal Berita Ilmu Keperawatan, 2008)
Research background is coverage result immunize Public Health Service and Social of Sub-Province Boyolali showing, happened by the degradation coverage percentage of immunize.Target of this research is check the factors influencing equipment the base immunize baby in Puskesmas Banyudono of Sub-Province Boyolali In line with the target, this research is including type of analytic observation method research with the transversal crosscut study approach or Cross Sectional. In this population research mother having childÂ  have age to 1 year and reside in Puskesmas region of Banyudono of Sub-Province Boyolali 2005 counted 491 baby. Technics sample intake of taken is Technique of intake sample by cluster is random from other side summed uply 100 responder. Method collecting data at research by kuesioner. Analysis technique used by linear double is regresi. Result of research show: (1) Storey; Level of mother education have the positive influence to equipment the base immunize, meaning that progressively goodness mount the mother education will have an effect on improve to the equipment the base immunize at baby, (2). House distance to Puskesamas don't have the influence to equipment the base immunize, (3). Mother knowledge the influence positive have to equipment the base immunize, meaning that progressively goodness mother knowledge will have an effect on to improve the equipment the base immunize at baby, (4) mother Motivation have the influence positip equipment the base immunize. meaning that progressively goodness motivate the mother will have an effect on to improve the equipment the base immunize at baby. Referring to this research result is suggested that : (1) Education require mother to be improved. Cause more and more high of education more and more big of baby possibility will be immunized completely. Make-Up of education can be done formally and also non-formal, (2) Effort of make-up of mother knowledge and motivate the mother will very useful, cause can improve the equipment immunize the baby